Development of tidal areas: Some principles and issues towards sustainability - Hyun, P.S.; Simm, J.; Ritzema, H. (Wiley, 2009)
The coastal zone comprises only 3% of the earth's surface, but contains a disproportionately high amount of its assets. Tidal areas include all those coastal areas where the tidal processes are capable of affecting man's activity or of being influenced by man. Tidal areas differ greatly depending on their location, geophysical conditions, climate, tidal range and cultural differences. Throughout the world, tidal areas have been and are being developed. These developments will continue as food production will need to be doubled in the next 25 years. To address questions related to a sustainable development of tidal areas, the International Commission of Irrigation and Drainage (ICID) established the Working Group on Sustainable Development of Tidal Areas in 2001. The working group has studied these questions and formulated principles and issues for sustainable development of tidal areas based on the relevant international conventions. The aim of this paper is to represent the official position of ICID and to support the preparation of the ICID Handbook Towards Sustainable Development of Tidal Area: Some Principles and Experiences.